THE EFFECT OF DEFENSE SPENDING ON PRIVATE INVESTMENT IN INDONESIA BASED ON HISTORICAL DATA FOR THE PERIOD 1981-2010 - Posma Sariguna Johnson Kennedy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Due to the crowding-out effect, defense spending can disrupt private investment. The purpose of this study is to examine the effect of defense spending, interest rates, and national taxes on private investment in Indonesia during the 1981-2010 period. A mathematical model was constructed to capture the impact of defense spending, non-military spending, private output, national interest rates, and taxes on private investment. By applying the regression processing econometric model, it can be seen that defense spending, non-military spending, changes in national taxes, and interest rates have a negative impact on private investment but are not too elastic. At the same time, changes in private-sector production output have a significant positive impact on private investment.